2009
DOI: 10.1093/ejechocard/jen315
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional strain and strain rate imaging of the right ventricle in adult patients before and after percutaneous closure of atrial septal defects

Abstract: Two-dimensional strain appears to be helpful also for the assessment of RV function and its response to correction of volume overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 10 publications
5
55
2
3
Order By: Relevance
“…16 Jategaonkar et al showed that RV volume overload was associated with increased S values, which returned to normal after abolishment of the volume overload, whereas SR was found to be less preloaddependent. 17 Their findings represent chronic preload changes in the RV as patients were examined before and 3 months after ASD closure. To our knowledge, ours is the first human study to examine the effect of acute preload reduction on 2DST parameters of the systemic RV.…”
Section: Effect Of Preload Changes On Strain and Srmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Jategaonkar et al showed that RV volume overload was associated with increased S values, which returned to normal after abolishment of the volume overload, whereas SR was found to be less preloaddependent. 17 Their findings represent chronic preload changes in the RV as patients were examined before and 3 months after ASD closure. To our knowledge, ours is the first human study to examine the effect of acute preload reduction on 2DST parameters of the systemic RV.…”
Section: Effect Of Preload Changes On Strain and Srmentioning
confidence: 99%
“…There have been conflicting results regarding the load sensitivity of the strain and SR of the RV when measured by Doppler 16 and speckle tracking studies. 17 The objectives of this study were to assess the effect of acute preload reduction and increased inotropy on 2D longitudinal strain and SR in patients with HLHS and relate these parameters to simultaneously derived load-independent measures of ventricular function measured by conductance catheter technique.…”
mentioning
confidence: 99%
“…Using a dedicated, customized software package (EchoPAC, Vingmed, General Electric, Horten, Norway), 2D strain was measured as previously described [27]. By tracing the endocardial contour on an end-diastolic frame, the software allows to track the contour on subsequent frames automatically.…”
Section: Strain Measurementsmentioning
confidence: 99%
“…Cerrahi kapatılmasından sonra zaman içinde sol ventrikül dilatasyonu geriler. Hacim değişiklikleri ile kardiyak fonksiyonlarda oluşan değişiklikler sıklıkla atriyal septal defekt kapatılması sonrası değerlendirilmiştir (12)(13)(14)(15). Ventriküler septal defektlerin perkütan kapatılması ile miyokardiyal gerilme kuvvetleri arasındaki ilişkiyi araştıran bir çalışma hem yetişkin hemde çocukluk çağında halen gerçekleştirilmemiştir.…”
Section: Discussionunclassified
“…Transkateter atriyal septal defekt kapatılmadan önce ve sonra longitidunal strain ve SRI ölçülen bir başka çalışmada da SRI değerlerinin hacim ile değişmediğini göstermiştir. Fakat bizim çalışmamızdan farklı olarak yüklenmenin azalması ile strain değerlerinde azalma göstermişlerdir (12).…”
Section: Discussionunclassified